MUSLIM PEKERJA DI PETERNAKAN BABI DALAM TINJAUAN SOSIOLOGI HUKUM ISLAM DAN EKONOMI ISLAM: Study Kasus di Desa Arjowilangun Kalipare Kabupaten Malang - Ahmad Muhtar Syarofi (Jurnal Penelitian Ilmiah INTAJ, 2023)
This study aims to find out about the Job Perceptions of Muslim workers in pig farms in Arjowinangun Kalipare Malang to fulfill their daily needs and their employment problems in perspective of Islamic law. It is a qualitative descriptive field research. The data sources used by researchers are primary data sources and secondary data sources. Data collection techniques used in this study were interviews and documentation. The data analysis technique used is qualitative analysis using inductive thinking methods. The results of the study show that the wages of Muslim workers in pig farms from the perspective of Islamic Law are not permissible even though they are economically very profitable and promising. It is reasonable that the level of dlarÅ«riyyÄt must still be prioritized because working in this place, the longer it lasts, can damage one's faith as a Muslim whereas pork in Islamic law is a type of severe uncleanness. Moreover his work is always interacting with pigs.